2022
DOI: 10.3389/fmicb.2022.959726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound small peptides of Chinese medicine on intestinal immunity and cecal intestinal flora in CTX immunosuppressed mice

Abstract: The study was designed to explore the improvement effect of CSPCM (compound small peptide of Chinese medicine) on intestinal immunity and microflora through the treatment of different doses of CSPCM. A total of 100 male Kunming mice were weighed and divided into five groups, namely, group A (control group), group B (model group), group C (0.1 g/kg·bw CSPCM), group D (0.2 g/kg·bw CSPCM), and group E (0.4 g/kg·bw CSPCM). The use of CTX (cyclophosphamide) caused a series of negative effects: the secretion of IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The longer the villi, the more contact with nutrients, resulting in higher efficiency of nutrient deposition. 36 The crypt depth reflects the colonization rate and maturity of crypt cells. The…”
Section: Discussionmentioning
confidence: 99%
“…The longer the villi, the more contact with nutrients, resulting in higher efficiency of nutrient deposition. 36 The crypt depth reflects the colonization rate and maturity of crypt cells. The…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that Bacteroidetes was related to the improvement effect of the compound small peptide of Chinese medicine on intestinal immunity in mice [44]. Moreover, Burkholderia, which belonged to Proteobacteria, in intestinal contents of fish was increased by the growth- promoting traditional Chinese medicine treatment [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, peptides derived particular, one of the most vital bioactivities of food-derived bioactive peptides is the immunomodulatory activity, which has already been extensively reported. For example, peptides derived from Chinese medicine can enhance intestinal immunity and adjust the balance of cecum intestinal flora in immunosuppressed mice [16]. Pan et al concluded that hydrolysates from milk protein could boost immune function in mice by reducing the level of IL-4 and increasing growth factor-β levels in serum [17].…”
Section: Introductionmentioning
confidence: 99%